Ideology conveyed via the material(ity) of picturebooks - Yannicopoulou, Angela (Array, 2019)
Picturebooks transmit messages through words and images and even through their format, but they transmit subtle subtext through their materiality. This paper examines how the material of the book-object is intentionally manipulated to contribute to an ideological significance of a picturebook as it complements and occasionally even contradicts the messages transmitted through words and pictures. This study reviews several picturebooks that use the materiality of the book as a moralising mechanism intended to expose the reader to the life lesson that as a member of society the responsibility for the environment and righting social injustices falls on all of us.